SH!TIFICATION or the Tendency to Fix the Wrong Things - Diana Derval Derval (NUST Business Review, 2023)
Abstract When facing crucial decision-making, many managers tend to fix the wrong things, leading to a SH!TIFICATION of the products and customer experiences. This article reviews eleven SH!TIFICATION tendencies we have and provides recommendations on how to overcome them. A particular focus is given to the silent update tendency, which consists in making changes without telling customers. The changes are not supposed to have an impact on the customer experience, but the chocolate bar and the GPS navigation cases highlight how and why these silent